Coated filter
By applying the wall-mounted carrier coating on the whole product and spraying the powder coating of inorganic particles and silicone resins, the problem of low filtration efficiency of existing particulate filters during initial use and regeneration is solved, and a higher level of filtration is achieved water resistance and filtration efficiency.
Patent Information
- Application Number
- CN202380049139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-11
AI Technical Summary
Particulate matter filters emitted by existing diesel and gasoline engines are inefficient in filtration during first use and during regeneration, and are difficult to maintain efficient filtration when loaded with smoke.
A coated monolithic article is employed, coated with a wall carrier coating, and a powder coating is formed thereon, which contains inorganic particles and silicone resins between 50:1 and 1:9.
The water resistance and filtration efficiency of the filter are improved, and especially during the first use and regeneration process, particulate matter can be filtered more effectively.
Smart Images

Figure CN119421747A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a powder-coated article for filtering particulate matter in exhaust gas. The powder-coated article includes a coated monolithic article and a powder coating on the coated monolithic article. The coated monolithic article is a monolithic article coated with a wall carrier coating, and the powder coating comprises inorganic particles and a silicone resin in a ratio between 50:1 and 1:9. The present disclosure also relates to a method of forming a powder-coated article as described herein. Background Art
[0002] There are issues regarding the emission of particulate matter (PM), commonly referred to as soot, from internal combustion engines, especially diesel and gasoline engines in automotive applications. The main issues are associated with potential health effects, particularly with very small particles with sizes in the nanometer range.
[0003] Diesel particulate filters (DPF) and gasoline particulate filters (GPF) have been manufactured using a variety of materials (including sintered metals, ceramics or metal fibers, etc.), of which the most common type in actual large-scale production is a wall-flow type made of porous ceramic materials, which are manufactured in the form of a monolithic array of many small channels extending along the length of the body. The alternating channels are blocked at one end, so the exhaust gas is forced to pass through the porous ceramic channel wall, which prevents most of the particles from passing through, so only the filtered gas enters the environment. Ceramic wall-flow filters in commercial production include those made of cordierite, various forms of silicon carbide and aluminum titanate. The actual shape and size of the practical filter on the vehicle and the characteristics such as the thickness of the channel wall and its porosity depend on the application of interest. The average size of the pores in the filter channel wall of the ceramic wall-flow filter through which the gas passes is typically in the range of 5μm to 50μm and is usually about 20μm. In sharp contrast, most diesel particulate matter of high-speed diesel engines of modern passenger cars is much smaller in size, such as 10nm to 200nm.
[0004] Some PM may remain within the pore structure in the filter wall, and this can gradually accumulate in some applications until the pores are bridged by a network of PM, and this PM network then enables easy formation of a particle cake on the inner walls of the filter channels. The particle cake is an excellent filter medium, and its presence provides very high filtration efficiency. In some applications, the soot is continuously burned on the filter as it is deposited, which prevents the particle cake from accumulating on the filter.
[0005] For some filters, such as light-duty diesel particulate filters, it is necessary to periodically remove trapped PM from the filter to prevent the buildup of excessive back pressure, which is detrimental to engine performance and can result in poor fuel economy. Therefore, in diesel applications, retained PM is removed from the filter by burning it in the air in a process during which the amount of available air and the amount of excess fuel used to reach the high temperatures required to ignite the retained PM are very carefully controlled. Towards the end of this process, which is generally referred to as regeneration, the removal of the last remaining particles in the filter can result in a significant reduction in filtration efficiency and the release of a burst of many small particles into the environment. As a result, the filter may have low filtration efficiency when first used and subsequently after each regeneration event and also during the latter part of each regeneration process.
[0006] Therefore, it is desirable to improve and / or maintain filtration efficiency at all times, such as during the early life of a filter when it is first used, and / or during and immediately after regeneration, and / or when the filter is loaded with soot.
[0007] WO 2021 / 028692 (the entire contents of which are incorporated herein by reference) describes a vehicle exhaust filter comprising a porous substrate having an inlet face and an outlet face, the porous substrate comprising an inlet channel extending from the inlet face and an outlet channel extending from the outlet face; the inlet channel and the outlet channel are separated by a plurality of filter walls having a porous structure; the vehicle exhaust filter is loaded with a refractory powder, the refractory powder having a tap density of less than 0.10 g / cm before loading 3 ; The vehicle exhaust filter has a mass loading of refractory powder of less than 10 g / L; and wherein greater than 40% of the refractory powder is located within the porous structure of the plurality of filter walls, and less than 60% of the refractory powder is coated on the outer surface of the plurality of filter walls. WO 2021 / 028692 also describes suitable methods and apparatus for spraying dry refractory powders, such as dry particulate aerosols, onto channels of a porous substrate, preferably wherein greater than 50% of the refractory powder, optionally up to 100% of the refractory powder may be located with the porous structure of the plurality of filter walls.
[0008] The inventors have developed the present invention in order to mitigate and / or overcome the problems observed in the prior art. The present invention provides an improved method for producing a more efficient coated monolithic article that advantageously exhibits higher water resistance and improved filtration efficiency. Summary of the invention
[0009] The present invention relates to a powder-coated article, comprising a coated monolithic article and a powder coating on the coated monolithic article. The coated monolithic article is a monolithic article coated with an on-wall carrier coating, and the powder coating comprises inorganic particles and an organic silicone resin in a ratio between 50:1 and 1:9.
[0010] The present invention also relates to a method of forming the coated monolithic article and a calcined powder coated article.
[0011] The present invention also relates to a powder-coated article / calcined powder-coated article for treating exhaust gas, and a vehicle exhaust system comprising the powder-coated article / calcined powder-coated article. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The filtration efficiency of a standard (in-wall) coated monolith, a (on-wall) coated monolith and a powder-coated monolith according to the invention is shown.
[0013] Figure 2 The filtration efficiency of a standard (in-wall) monolith, a (on-wall) coated monolith, an in-wall coated monolith with a powder coating and a powder coated monolith according to the invention are shown. DETAILED DESCRIPTION
[0014] In one embodiment, the present invention relates to a powder-coated article comprising:
[0015] a) a coated monolithic article, and
[0016] b) powder coating on coated monolithic articles,
[0017] wherein the coated monolithic product is a monolithic product coated with a wall coating,
[0018] And the powder coating comprises inorganic particles and silicone resin in a ratio between 50:1 and 1:9.
[0019] In another embodiment, the invention relates to a method of forming a powder coated article as described herein, the method comprising:
[0020] i) providing a coated monolithic article,
[0021] ii) spraying the inorganic particles and the silicone resin as a dry particulate aerosol onto the coated monolithic article to form a powder coating,
[0022] The ratio of the inorganic particles to the silicone resin is between 50:1 and 1:9.
[0023] In another embodiment, the present invention is directed to a calcined powder coated article comprising:
[0024] a) a coated monolithic article, and
[0025] b) a calcined powder coating on a coated monolithic article, wherein the coated monolithic article is a monolithic article coated with a wall coating,
[0026] And the calcined powder coating comprises inorganic particles and silicon dioxide in a ratio between 65:1 and 1:7.
[0027] In another embodiment, the present invention is directed to a powder coated article or a calcined powder coated article as described herein for use in treating exhaust gas.
[0028] In another embodiment, the present invention is directed to a vehicle exhaust system comprising a powder coated article or a calcined powder coated article as described herein.
[0029] The present disclosure will now be further described. In the following paragraphs, different aspects / embodiments of the present disclosure are defined in more detail. Unless there is a clear contrary description, each aspect / embodiment so defined may be combined with any other aspect / embodiment or multiple aspects / embodiments. In particular, any feature indicated as being preferred or advantageous may be combined with any other one or more features indicated as being preferred or advantageous.
[0030] Coated monolithic articles
[0031] The monolithic article is a coated monolithic article. The coating comprises one or more washcoats, preferably catalytic washcoats. Washcoats are compositions that coat the porous structure of the article. The article comprising the one or more washcoats is then preferably calcined before the inorganic particles and the silicone resin are sprayed onto the channels as described herein.
[0032] The catalytic washcoat may include a catalyst selected from the group consisting of a hydrocarbon trap, a three-way catalyst (TWC), a NOx absorber, an oxidation catalyst, a selective catalytic reduction (SCR) catalyst, a lean NOx catalyst, and a combination of any two or more thereof. The catalysts (e.g., TWC, NOx absorber, oxidation catalyst, hydrocarbon trap, and lean NOx catalyst) may contain one or more platinum group metals, particularly those selected from the group consisting of platinum, palladium, and rhodium.
[0033] Thus, the coated monolithic article may be, for example, a catalyzed soot filter (CSF), a selective catalytic reduction filter (SCRF), a lean NOx trap filter (LNTF), a gasoline particulate filter (GPF), an ammonia slip catalyst filter (ASCF), or a combination of two or more thereof (e.g., a filter comprising a selective catalytic reduction (SCR) catalyst and an ammonia slip catalyst (ASC)).
[0034] The coated monolithic article is coated with an on-wall coating. "On-wall" means that the carrier coating is present as a coating on the wall of the monolithic article. The coating may be present on the wall of the monolithic article at a thickness of about 0.1% to 50% (e.g., 0.1% to 30% or 0.5% to 15%) of the thickness of the wall on which the coating is disposed. Some of the on-wall coating may be present within the wall. "In-wall" means that the carrier coating is present in pores within the porous monolithic article.
[0035] The monolithic article may include a plurality of channels for the passage of exhaust gas, each channel having a gas contact surface. Monolithic articles are well known in the art. Monolithic articles may sometimes be referred to as substrates, preferably honeycomb substrates, preferably ceramic honeycomb substrates. Such substrates include a plurality of channels suitable for the passage of exhaust gas. The channels are parallel and extend from the inlet end (or first end) to the outlet end (or second end), i.e., the channels extend axially through the article. Adjacent channels may be alternately blocked at each end of the monolithic article so that in use, the exhaust gas passes along the inlet channel (i.e., the channel for receiving the exhaust gas that opens at the inlet end of the monolithic article) and is forced through the channel wall into the adjacent outlet channel (i.e., the channel that opens at the outlet end of the monolithic article). The monolithic article may include a plurality of inlet channels and a plurality of outlet channels. Typically, the channel has a square cross-section, but any known monolithic design may also be used.
[0036] In a preferred embodiment, 15%-100% of the washcoat loading of the entire monolithic article is present on the walls, preferably 16%-99%, 17%-95%, 18%-90%, 19%-80% or 20%-75%. In an alternative embodiment, at least 15%, at least 16%, at least 17%, at least 17%, at least 18%, at least 19%, at least 20%, at least 21%, at least 22% or at least 25% of the washcoat loading of the entire monolithic article is present on the walls. In a particularly preferred embodiment, at least 15% or at least 20% of the washcoat loading of the entire monolithic article is present on the walls.
[0037] In a preferred embodiment, 50%-100% of the load of the washcoat in the inlet channel of the monolithic article is present on the wall, preferably 55%-99%, 60%-95%, 65%-92%, 70%-90% or 80%-90%. In an alternative embodiment, at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90% or at least 95% of the load of the washcoat in the inlet channel of the monolithic article is present on the wall. In a particularly preferred embodiment, at least 80% or at least 90% of the load of the washcoat in the inlet channel of the monolithic article is present on the wall.
[0038] In a preferred embodiment, 5%-100% of the components (e.g., articles, inlet channels and / or outlet channels) are coated with a wall washcoat. Preferably, 5% to 100%, 10% to 99%, 20% to 98%, 30% to 97%, 40% to 96%, 50% to 95%, 60% to 94%, 70% to 93%, 80% to 90% of the components are coated with a wall washcoat, for example, at least 5%, at least 20%, at least 50%, at least 60%, at least 70%, at least 75% or at least 80% of the components are coated with a wall washcoat.
[0039] As will be appreciated by those skilled in the art, the percentage of coating present "on the wall" can be determined by techniques in the art such as scanning electron microscopy (SEM) or optical microscopy.
[0040] In some embodiments, the coated monolithic article is coated with a wall washcoat having one or more of the following characteristics:
[0041] 1)d 90 5 μm-30 μm, for example 10 μm-28 μm, 15 μm-25 μm, preferably about 20 μm,
[0042] 2) Viscosity is 5cPs-1500cPs, such as 10cPs-1400cPs, 50cPs-1300cPs, 100
[0043] cPs-1200cPs, 200cPs-1100cPs, 300cPs-1000cPs, 400cPs-950cPs,
[0044] 500cPs-900cPs, 550cPs-850cPs, 600cPs-800cPs, 650cPs-750
[0045] cPs, preferably about 700 cPs,
[0046] 3) pore formers, such as cellulose pore formers, for example, selected from Arbocel, Vivapur,
[0047] Pore former for Mipelon PM-200, Propyltex, Orgasol and Remyrise.
[0048] It has been found that the use of one or more of the above features can help to facilitate the formation of a coating on the wall.
[0049] Viscosity can be measured at 20°C on a Brookfield RV DVII+ Extra Pro viscometer using a SC4-27 spindle at a spindle speed of 50 rpm.
[0050] The support coating that can be used to coat the monolithic article with the wall coating preferably comprises a zeolite (e.g., a metal-loaded zeolite), a binder, and a pore former. Examples of zeolites include small, medium, or large pore zeolites, such as CHA, AEI, FAU, FER, and MFI. When a metal-loaded zeolite is used, the metal can be selected from transition metals, such as one or more of Cu, Ce, Fe, and Mn. Examples of binders are alumina binders, such as boehmite, alpha alumina, beta alumina, and gamma alumina. Examples of pore formers include cellulose pore formers, polyethylene, starch, graphite, polypropylene, polyaramide, polytetrafluoroethylene, polystyrene, cellulose fibers, and polymethyl methacrylate, such as Arbocel, Vivapur, Mipelon PM-200, Propyltex, Orgasol, and Remyrise. In some embodiments, the zeolite and the pore former are present in a ratio of 10: 1 to 1: 3, preferably 8: 1 to 1: 2, 6: 1 to 1: 1.5, 5: 1 to 1: 1, 4: 1 to 1.5: 1, 3: 1 to 2: 1, such as 5: 1 to 1: 2 or 3: 1 to 1: 1. In some embodiments, the zeolite and the binder (e.g., an alumina binder) are present in a ratio of 20: 1 to 1: 1, such as 15: 1 to 2: 1, preferably 12: 1 to 3: 1, such as 10: 1 to 5: 1, more preferably about 9: 1.
[0051] Preferably, the washcoat loading of the coated monolithic article is between 0.1 g / in 3 and 10g / in 3 Between, preferably between 0.1g / in 3 and 8g / in 3 Between 0.5g / in 3 and 7g / in 3 Between 0.8g / in 3 and 6g / in 3 Between 1g / in 3 and 5g / in3 Between 1.25g / in 3 and 4g / in 3 Between 1.5g / in 3 and 3g / in 3 Between 2g / in 3 and 2.5g / in 3 In a more preferred embodiment, the washcoat loading of the coated monolithic article is between 0.5 g / in 3 and 5g / in 3 Between or 1g / in 3 and 2.5g / in 3 between.
[0052] The monolithic article / substrate may be formed, for example, from sintered metals, ceramics, or metal fibers, etc. For example, the article may be formed from cordierite, various forms of silicon carbide, or aluminum titanate.
[0053] In some embodiments, the monolithic article is a monolithic filter. It is particularly preferred that the monolithic filter is a wall-flow filter (also referred to as a wall-flow monolithic article). Wall-flow filters are well known, and typically, adjacent channels are alternately blocked at each end of the monolithic article so that, in use, exhaust gases pass along the inlet channel (i.e., the channel opening at the inlet end of the monolithic article for receiving the exhaust gases) and are forced through the channel wall into the adjacent outlet channel (i.e., the channel opening at the outlet end of the monolithic article).
[0054] The channel walls have a pore distribution that provides the desired porosity for the monolithic article, with the average size of the pores in the channel walls (e.g., filter walls) typically being in the range of 5 μm to 50 μm. Each channel has a gas-contacting surface. That is, each channel has a surface suitable for contacting exhaust gases, for example, when in use. The surface may be provided by the channel wall surface and / or the pores contained therein.
[0055] In another particularly preferred embodiment, the monolithic article is a catalyst article (ie, a catalytic article). Catalytic monolithic articles are well known and exhibit properties such as oxidation, NO x - Catalytic function of capture or selective catalytic reduction activity.
[0056] In a particularly preferred embodiment, the monolithic article is a catalyzed wall-flow filter. Thus, the article may be, for example, a catalyzed soot filter (CSF), a selective catalytic reduction filter (SCRF), a lean NO xa trap filter (LNTF), a gasoline particulate filter (GPF), an ammonia slip catalyst filter (ASCF), or a combination of two or more thereof (eg, a filter including a selective catalytic reduction (SCR) catalyst and an ammonia slip catalyst (ASC)).
[0057] The shape and size of the filter (e.g., characteristics such as channel wall thickness and its porosity) can vary depending on the intended application of the filter. The filter can be configured for use with an internal combustion engine to filter exhaust gases emitted by the internal combustion engine. The internal combustion engine can be a gasoline spark ignition engine. However, the filter has specific applications when configured for use with an internal combustion engine in the form of a diesel or gasoline engine.
[0058] Powder coating
[0059] A powder coating is present on the coated monolithic article. The powder coating comprises inorganic particles and silicone resin in a weight ratio of between 50:1 and 1:9. In a preferred embodiment, the weight ratio of inorganic particles to silicone resin is between 40:1 and 1:8, between 30:1 and 1:7, between 20:1 and 1:6, between 10:1 and 1:5, between 9:1 and 1:4, between 8:1 and 1:3, between 7:1 and 1:2, between 6:1 and 1:1, between 5:1 and 2:1, or between 4:1 and 3:1. In a further preferred embodiment, the weight ratio of inorganic particles to silicone resin is between 10:1 and 1:3, preferably between 5:1 and 1:2, more preferably between 4:1 and 1:1, for example about 3:1.
[0060] Without wishing to be bound by theory, the present inventors have discovered that a specific ratio of inorganic particles to silicone resin can result in higher filtration efficiency and improved stability.
[0061] Preferably, the inorganic particles are selected from the group consisting of zeolites, refractory oxides and mixtures thereof, preferably zeolites.
[0062] Zeolite is a structure formed by alumina and silica, and the SAR determines the reactive sites within the zeolite structure. The zeolite can be a small pore zeolite (e.g., a zeolite with a maximum ring size of eight tetrahedral atoms), a medium pore zeolite (e.g., a zeolite with a maximum ring size of ten tetrahedral atoms), or a large pore zeolite (e.g., a zeolite with a maximum ring size of twelve tetrahedral atoms), or a combination of two or more thereof.
[0063] Examples of suitable zeolites include silicate zeolites, aluminosilicate zeolites, metal-substituted aluminosilicate zeolites, AlPO, MeAlPO, SAPO, MeAPSO, etc. In some embodiments, the zeolite is selected from aluminosilicate zeolites, borosilicate zeolites, gallosilicate zeolites, SAPO zeolites, AlPO zeolites, MeAPSO zeolites, and MeAPO zeolites.
[0064] In the case where the zeolite is a small pore zeolite, the small pore zeolite may have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, GIS, GOO, IHW, ITE, ITW, LEV, LTA, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SFW, SIV, THO, TSC, UEI, UFI, VNI, YUG, and ZON, or a mixture and / or combination and / or intergrowth of two or more thereof. In some embodiments, the small pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) CHA, LEV, AEI, AFX, ERI, LTA, SFW, KFI, DDR, and ITE. In some embodiments, the small pore zeolite has a framework structure selected from the group comprising (eg, consisting of): CHA and AEI. The small pore zeolite can have a CHA framework structure.
[0065] In the case where the zeolite is a mesoporous zeolite, the mesoporous zeolite may have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, -PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, -SVR, SZR, TER, TON, TUN, UOS, VSV, WEI and WEN, or a mixture and / or intergrowth of two or more thereof. In some embodiments, the medium pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) FER, MEL, MFI, and STT. In some embodiments, the medium pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) FER and MFI, specifically MFI. When the medium pore molecular sieve has a FER or MFI framework, the zeolite may be ferrierite, silica rock, or ZSM-5.
[0066] In the case where the zeolite is a large pore zeolite, the large pore zeolite can have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, MEI, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, -RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY, and VET, or a mixture and / or intergrowth of two or more thereof. In some embodiments, the large pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) AFI, BEA, MAZ, MOR, and OFF. In some embodiments, the large pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) BEA, MOR, and FAU. When the macroporous molecule has a framework structure of FTC BEA, FAU, or MOR, the zeolite may be beta zeolite, faujasite, Y-type zeolite, X-type zeolite, or mordenite.
[0067] In some embodiments, the zeolite has a framework type selected from the group consisting of ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, SCO, C FI, SGF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IFY, IHW, IRN, ISV, ITE, ITH, ITW, IWR, IWW, JBW, KFI, LAU , LEV, LIO, LIT, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, MSO, MTF, MTN, M TT, MTW, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OSI, OSO, OWE, PAR, PAU, PHI, PON, RHO, RON, RRO, RSN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFW, SGT, SOD, SOS , SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, WI, VNI, VSV, WIE, WEN, YUG, ZON, or their combination. In some embodiments, the zeolite has a framework type selected from the group consisting of AEI, AFT, AFV, AFX, AVL, BEA, CHA, DDR, EAB, EEI, ERI, FAU, FER, IFY, IRN, KFI, LEV, LTA, LTN, MER, MOR, MWF, MFI, NPT, PAU, RHO, RIE, RTH, SAS, SAT, SAV, SFW, TSC, and UFI.
[0068] In another embodiment, the inorganic particles are refractory oxide particles, which may be based on an oxide selected from the group consisting of: alumina, silica, zirconia, ceria, chromia, magnesia, calcium oxide, titania, and mixed oxides of any two or more thereof. Preferably, the refractory oxide particles include calcium aluminate, fumed alumina, fumed silica, fumed titania, fumed zirconia, fumed ceria, alumina aerogel, silica aerogel, titania aerogel, zirconia aerogel, ceria aerogel or mixtures thereof. The one or more refractory powders (refractory oxide particles) may be produced by a pyrometallurgical process, such as flame pyrolysis.
[0069] Preferably, the inorganic particles have a d 90 (by volume) between 0.1 μm and 100 μm, preferably between 0.2 μm and 50 μm, between 0.5 and 40 μm, between 1 μm and 30 μm, between 2 μm and 20 μm, between 5 μm and 15 μm, between 6 μm and 10 μm. In a preferred embodiment, the inorganic particles have a d 90 (by volume) between 0.1 μm and 30 μm, between 0.5 μm and 20 μm or between 1 μm and 10 μm.
[0070] Preferably, the crystallite size of the inorganic particles is 0.05 μm to 10 μm, preferably 0.1 μm to 8 μm, 0.5 μm to 6 μm, 0.75 μm to 5 μm, 1 μm to 4 μm, or 2 μm to 3 μm. In a particularly preferred embodiment, the crystallite size of the inorganic particles is 0.8 μm to 2.5 μm, for example 1 μm to 2 μm.
[0071] Particle size can be measured by standard methods, such as scanning electron microscopy (SEM) and laser diffraction. If the particle size measurement is obtained by laser diffraction particle size analysis, it is done using a Malvern Mastersizer 3000, which is a volume-based technology (i.e., D(v, 0.1), D(v, 0.5), D(v, 0.9) and D(v, 0.98) may also be referred to as DV10, DV50, DV90 and DV98 (or D10, D50, D90 and D98, respectively), and the Mie mathematical theoretical model is applied to determine the particle size distribution.
[0072] The silicone resin that can be used in the present invention is an oligosiloxane. Examples of the silicone resin that can be used in the present invention are one or more of the following: polysilsesquioxanes or polysiloxanes, such as: polyalkylsilsesquioxanes (e.g., polymethylsilsesquioxanes), polyphenylsiloxanes, polyalkylsiloxanes (e.g., polymethylsiloxanes), and polyphenylsiloxanes.
[0073] The silicone resin may be referred to herein as silicone resin particles. Preferably, the silicone resin has a melting point of less than 150° C., preferably less than 100° C., less than 90° C., less than 85° C., or less than 80° C. Without wishing to be bound by theory, the inventors believe that silicone resins having such a melting point are particularly suitable for powder coating processes, i.e., for effective dispersion of microparticles along with inorganic particles on a monolithic article, while the melting point is low enough to allow low temperature calcination, thereby effectively and efficiently adhering the inorganic particles to the gas-contacting surfaces of the channel walls.
[0074] Preferably, the silicone resin (ie, silicone resin particles) has a d 90 (by volume) between 0.1 μm and 100 μm, preferably between 0.2 μm and 50 μm, between 0.5 μm and 40 μm, between 1 μm and 30 μm, between 2 μm and 20 μm, between 5 μm and 15 μm, between 6 μm and 10 μm. In a preferred embodiment, the d 90 (by volume) between 0.1 μm and 30 μm, between 0.5 μm and 20 μm or between 1 μm and 10 μm.
[0075] Preferably, the mass loading of the powder coating (e.g., the total mass loading of the powder coating) is between 0.1 g / L and 50 g / L, such as between 0.5 g / L and 45 g / L, between 1 g / L and 40 g / L, between 2 g / L and 30 g / L, or between 5 g / L and 25 g / L. Preferably, the mass loading of the inorganic particles is between 0.05 g / L and 40 g / L, such as between 0.1 g / L and 30 g / L, between 1 g / L and 25 g / L, between 5 g / L and 20 g / L, or between 10 g / L and 15 g / L. Preferably, the mass loading of the silicone resin is between 0.05 g / L and 30 g / L, such as between 0.1 g / L and 25 g / L, between 0.5 g / L and 20 g / L, between 1 g / L and 15 g / L, or between 5 g / L and 10 g / L. By way of example, in the case of a 1:1 weight ratio of inorganic particles to silicone resin, the loading of inorganic particles may be 10 g / L and the loading of silicone resin may be 10 g / L, resulting in a total loading of 20 g / L for the powder coating. By way of example, in the case of a 2:1 ratio, the inorganic particle loading may be 10 g / L and the silicone resin loading may be 5 g / L, resulting in a total loading of 15 g / L.
[0076] Powder coating is on the coated article. "On" may mean that the powder coating is applied directly to the coated article, i.e., without an intervening layer, or may mean that the powder coating is on the coated article, but one or more intervening layers are present. In a preferred embodiment, the powder coating is applied directly to the coated article.
[0077] Method of forming a powder coated article
[0078] The method of forming a powder coated article as described herein comprises spraying inorganic particles and a silicone resin as a dry particle aerosol onto a coated monolithic article to form a powder coating. The method may include spraying a dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) onto a gas-contacting surface of a plurality of channels on the coated monolithic article. Spraying dry powder onto a monolithic article is known in the art. Suitable methods and apparatus are described, for example, in WO 2011 / 151711, WO 2021 / 028692, and WO 2021 / 028691.
[0079] In a preferred embodiment, the spraying step comprises a first spraying step, wherein the inorganic particles are sprayed onto the coated monolithic article as a first dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) to form an inorganic particle layer, and in a second spraying step, the silicone resin is then sprayed onto the inorganic particle layer as a second dry powder (i.e., dry microparticles) suspended in a gas (i.e., as an aerosol) to form a coating. Thus, the inorganic particles are sprayed onto the coated monolithic article, and then the silicone resin is separately sprayed onto the coated monolithic article further coated with the inorganic particles.
[0080] In a preferred embodiment, the spraying step includes a first spraying step, wherein the silicone resin is sprayed onto the coated monolithic article as a first dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) to form a silicone resin layer, and in a second spraying step, inorganic particles are then sprayed onto the silicone resin layer as a second dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) to form a coating. Thus, the silicone resin is sprayed onto the coated monolithic article, and then the inorganic particles are separately sprayed onto the coated monolithic article further coated with the silicone resin.
[0081] Even more preferably, the mixture of the inorganic particles and the silicone resin is sprayed onto the coated monolithic article as a dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) to form a powder coated article. Thus, the intimate mixture of the inorganic particles and the silicone resin is applied to the coated monolithic article and enhances the adhesion of the inorganic particles to the coated monolithic article when the silicone resin is calcined.
[0082] In an alternative embodiment, the inorganic particles and the silicone resin are sprayed onto the coated monolithic article as a dry powder (i.e., dry particles) suspended in a gas (i.e., as an aerosol) to form a powder-coated article. In this embodiment, the inorganic particles and the silicone resin are applied to the coated monolithic article separately and simultaneously.
[0083] The term "dry powder" or "dry granules" refers to a particulate composition that is not suspended or dissolved in a liquid. This does not necessarily mean that all water molecules are completely absent. The dry powder / dry granules are preferably free-flowing.
[0084] In a preferred embodiment, the spraying step is performed at a constant gas flow rate, as described, for example, in WO2021 / 028692. The gas may be selected from one or more of air, nitrogen, argon, helium, oxygen, carbon dioxide, etc. In a preferred embodiment, the gas is air. In a particularly preferred embodiment, the gas flow rate is 50 m / s. 3 / hr and 2000m 3 / hr, for example 80m 3 / hr and 1500m 3 / hr, 100m 3 / hr and 1000m 3 / hr, 80m 3 / hr and 500m 3 / hr, for example 90m 3 / hr and 400m 3 / hr, 100m 3 / hr and 300m 3 / hr, 110m 3 / hr and 280m 3 / hr, 150m 3 / hr and 250m 3 / hr or 180m 3 / hr and 220m 3 In a further preferred embodiment, the gas flow rate is between 100m 3 / hr and 400m 3 / hr, for example 150m 3 / hr and 350m 3 / hr or 200m 3 / hr and 300m 3 / hr.
[0085] The inventors have surprisingly found that using a low air flow rate ensures that the powder coating is deposited as a uniform layer along the channel, with a greater build-up at the end of the article, filling the gap between the end of the powder coating and the end of the article.
[0086] The method may also include calcining the coating to provide a calcined powder coated article. That is, the method includes calcining a powder coating on which inorganic particles and an organosilicon resin are sprayed. The calcining step results in the organosilicon resin in the powder coating being calcined into silicon dioxide. In some embodiments, calcining results in about 100% of the silicone resin being calcined into silicon dioxide. In other embodiments, calcining results in at least 95%, 90%, 80%, 75%, 60% or 50% of the organosilicon resin being calcined into silicon dioxide.
[0087] The weight ratio of inorganic particles to silica in the calcined powder coating may be between 65:1 and 1:7. In a preferred embodiment, the weight ratio of inorganic particles to silica is between 50:1 and 1:6, between 38:1 and 1:6, between 25:1 and 1:5, between 13:1 and 1:4, between 11:1 and 1:3, between 10:1 and 1:2, between 9:1 and 1:1.5, between 8:1 and 1:0.8, between 6:1 and 3:1 or between 5:1 and 4:1. In a further preferred embodiment, the weight ratio of inorganic particles to silica is between 13:1 and 1:2, preferably between 6:1 and 1:1.5, more preferably between 5:1 and 1:0.8, for example about 2:1.
[0088] Preferably, the calcining step comprises heating to a temperature of at least 200° C., preferably at least 300° C., more preferably at least 400° C., and / or a temperature of at most 1000° C., at most 900° C., at most 800° C., at most 700° C., at most 600° C., preferably at most 550° C., more preferably at most 530° C. Thus, calcining preferably comprises heating to a temperature of 200° C. to 1,000° C., preferably 300° C. to 900° C., preferably 400° C. to 800° C., more preferably 400° C. to 700° C., even more preferably 450° C. to 550° C., for example about 500° C.
[0089] Such temperatures have been found to be optimal for forming an effective binder, thereby providing improved filtration efficiency and increased water resistance to the calcined powder coated article. Such temperatures are particularly advantageous when the coated monolithic article is a coated catalyst article, such as a coated catalytic wall-flow filter, because these temperatures allow the silicone resin to be calcined into a crosslinked silica without negatively affecting the catalytic efficiency (i.e., without degrading the coated catalyst article). Ideally, the calcination temperature is kept as low as possible to reduce the likelihood of affecting the catalytic activity of any catalyst present in the coated article.
[0090] The pore size of the calcined powder coating is preferably in the range of 1 μm to 100 μm, preferably 1 μm to 50 μm, more preferably 1 μm to 20 μm or 5 μm to 20 μm.
[0091] The pore size of the calcined powder can be measured by techniques in the art, for example by mercury porosimetry (MIP) on a Micromeritics Autopore instrument.
[0092] As used herein, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. The use of the term "comprising" is intended to be interpreted as including such features but not excluding other features, and is also intended to include feature options that must be limited to those described. In other words, the term also includes the limitations "essentially consisting of..." (intended to indicate that certain additional components may be present, provided that they do not substantially affect the basic characteristics of the described features) and "consisting of..." (intended to indicate that other features may not be included, so that if these components are expressed in percentages of their proportions, these will add up to 100%, taking into account any unavoidable impurities), unless the context clearly indicates otherwise.
[0093] As used herein, the term “ 90 "(by volume)" refers to the Malvern Panalytical with Aero s dispersion unit available from Malvern Panalytical Ltd., Malvern, UK. 3000 measured d 90 (by volume) Measurement results. Dispersion conditions: air pressure = 2 bar, feed rate = 65%, hopper gap = 1.2 mm. According to Malvern Set the refractive index and absorption parameters following the instructions provided in the 3000 User Manual.
[0094] As used herein, the term "g / L" (grams per liter) refers to the mass of powder divided by the volume of the filter.
[0095] The foregoing detailed description has been provided by way of explanation and illustration and is not intended to limit the scope of the appended claims. Many variations to the presently preferred embodiments shown herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.
[0096] Example
[0097] Carrier coating preparation
[0098] Carrier coating A :
[0099] A washcoat was prepared comprising a Cu-exchanged zeolite (CHA, SAR=18.5, supplied by Tosoh, Cu loading=3.3 wt%) and stabilized gamma alumina (supplied by PIDC) suspended in water at a ratio of 9:1. The washcoat had a d 90 TEAH was added at 4 wt% of the zeolite before the addition of alumina.
[0100] Carrier coating B :
[0101] A washcoat was prepared comprising Natrasol (cellulose thickener), Cu exchanged zeolite (CHA, SAR=18.5, Cu loading=3.3 wt%, supplied by Tosoh), Arbocel UFC100 (cellulose supplied by JRS), and boehmite (supplied by PIDC) suspended in water in a ratio of 9:5:1 (zeolite:arbocel:boehmite). The washcoat had a d 90 .
[0102] Carrier coating C :
[0103] A washcoat comprising a Cu exchanged zeolite (CHA, SAR=18.5, supplied by Tosoh, Cu loading=3.3 wt%) and stabilized gamma alumina (supplied by PIDC) suspended in water at a ratio of 9:1. The washcoat has a d90 of 4 μm-5 μm. The surface of the zeolite is modified using aminosilane (see US11192793B2).
[0104] Method for preparing an inner wall coated filter (Filter A) :
[0105] Washcoat application according to EP3122458. Washcoat C was applied to the outlet end of the filter (SC18 supplied by NGK) to coat 80% of the filter volume, with a calcined loading of 1.5 g.in relative to the total filter volume. -3 Washcoat A was applied to the inlet end of the filter to coat 30% of the filter volume, with a calcined loading of 0.6 g.in relative to the filter volume. -3 .
[0106] Method for preparing a wall-coated filter (Filter B) :
[0107] Washcoat application according to EP3122458. Washcoat A was applied to the outlet end of the filter (SC18 supplied by NGK) to coat 80% of the filter volume, with a calcined loading of 1.5 g.in relative to the filter volume. -3Washcoat B was applied to the inlet end of the filter to coat 80% of the filter volume, with a calcined loading of 0.6 g.in relative to the filter volume. -3 .
[0108] General method for preparing powder coated articles
[0109] Zeo(d 90 Chabazite with a d90 of 4 μm and a SAR of 23, purchased from Tosoh) and Silres Mk powder (d90 of 9 90 The obtained mixed powder was sprayed onto the (wall) coated filter (Filter A) from the inlet end under a constant air flow rate (using the spraying method of EP4013954A1). The air flow rate was 100-200m 3 The coated parts were then calcined to 500°C for 1 hour.
[0110] Example 1 - Ratio Study
[0111] Various ratios of zeolite to silicone resin were studied and the results are shown in Table 1.
[0112] Use compressed air to spray the inlet end, then use compressed air to spray the outlet end. Then calculate the mass loss.
[0113]
[0114] Table 1-Zeo is d 90 For CHA zeolite of 4 μm, Silres is d 90 9μm silicone resin .
[0115] Table 1 shows that the ratio of zeolite to silicone resin in the powder coating affects cold flow back pressure and stability. The mass loss indicates that the resulting film layer is unstable.
[0116] Example 2 - Filtration Efficiency Study
[0117] The filter efficiency was tested under various conditions. The first condition was an oven clean plus a cold start WLTC test (high quality), the second condition was a hot start WLTC test (high quality), and the third condition was a cold start WLTC (regeneration) test (low quality). WLTC is the World Light Duty Test Cycle, and the regeneration condition is an elevated temperature to break down the soot cake.
[0118] The results for the standard (in-wall) monolith (Filter A), the (on-wall) coated monolith (Filter B) and the powder coated monolith (3:1 Zeo:SilRes) are shown in Figure 1 middle.
[0119] Figure 1It is shown that under all test conditions the powder coated monolith article according to the present invention exhibits higher filtration efficiency compared to standard (in-wall) coated monolith and (on-wall) coated monolith articles.
[0120] Example 3 - Back Pressure
[0121] Prepare the following samples:
[0122] I 1:1Zeo:SilRes 45g
[0123] II 1:1Zeo:SilRes 60g
[0124] III 3:1Zeo:SilRes 60g
[0125] IV 1:1CuZeo2:SilRes 60g
[0126] where SilRes is a standard silicone resin MK material, Zeo2 is an AEI zeolite and the amounts given in g are the mass of powder applied to the monolith.
[0127] Samples I-IV were completely immersed in a container of about 6 L of deionized water for approximately 10 seconds, after which they were removed from the water, shaken to remove excess water and dried in an oven at 115° C. with air flow for approximately 45 minutes.
[0128] On Superflow Flowbench SF-1020 at 600m 3 The cold flow back pressure test was performed on samples I-IV before and after the water immersion treatment at a flow rate of 100 Å / h. The test results are shown in Table 2.
[0129] sample Initial CFBP / mbar Final CFBP / mbar Loss / mbar I 103.7 92.1 11.6 II 104 95.3 8.7 III 95.2 94.8 0.4 IV 103.6 92.9 10.7
[0130] Table 2
[0131] Table 2 shows that water immersion caused only a slight change in the back pressure of Sample III.
[0132] Example 4 - Filtration Studies
[0133] The filtration efficiency was tested and the results for the standard (in-wall) monolith (Filter A), the (on-wall) coated monolith (Filter B), the in-wall coated monolith with powder coating (Filter A+EFC) and the powder coated monolith (Filter B+EFC) are shown in Figure 2 EFC is an enhanced filter coating, i.e. a powder coating as described herein.
[0134] Figure 2It was shown that the powder coated monolith article according to the present invention exhibits a higher filtration efficiency compared to a standard (in-wall) coated monolith, an (on-wall) coated monolith article and an in-wall coated monolith with a powder coating.
Claims
1. A powder-coated product, comprising: a) a coated monolithic article, and b) a powder coating on said coated monolithic article, wherein the coated monolithic product is a monolithic product coated with a wall coating, And the powder coating comprises inorganic particles and silicone resin in a ratio between 50:1 and 1:
9.
2. The powder coated article according to claim 1, wherein the inorganic particles are zeolites, preferably small pore zeolites.
3. A powder coated article according to claim 1 or claim 2, wherein the inorganic particles are CHA zeolite.
4. The powder coated article according to any preceding claim, wherein the coated monolithic article is a coated monolithic filter, preferably a coated wall-flow filter, and / or a coated catalyst article, preferably a coated catalytic wall-flow filter.
5. A powder coated article according to any preceding claim, wherein the weight ratio of inorganic particles to silicone resin is between 10:1 and 1:3, preferably between 5:1 and 1:2, more preferably between 4:1 and 1:1, such as about 3:
1.
6. A powder coated article according to any preceding claim, wherein the inorganic particles and / or silicone resin particles have a d 90 (by volume) between 0.1 μm and 100 μm, preferably between 0.2 μm and 50 μm, between 0.5 μm and 40 μm, between 1 μm and 30 μm, between 2 μm and 20 μm, between 5 μm and 15 μm, between 6 μm and 10 μm.
7. A powder coated article according to any preceding claim, wherein the mass loading of the powder coating is between 0.1 g / L and 50 g / L, for example between 0.5 g / L and 45 g / L, between 1 g / L and 40 g / L, between 2 g / L and 30 g / L or between 5 g / L and 25 g / L.
8. A method of forming a powder coated article according to any preceding claim, the method comprising: i) providing a coated monolithic article, ii) spraying inorganic particles and silicone resin as a dry particulate aerosol onto the coated monolithic article to form a powder coating, The ratio of the inorganic particles to the silicone resin is between 50:1 and 1:
9.
9. The method according to claim 8, wherein the spraying step is performed under a constant gas flow rate, preferably wherein the gas flow rate is 80 m 3 / hr and 300m 3 / hr.
10. A method according to claim 8 or claim 9, wherein the method comprises the further steps of: iii) calcining the powder coating to provide a calcined powder coated article.
11. The method according to claim 10, wherein the calcining step comprises heating to a temperature of at least 200°C, preferably at least 300°C, more preferably at least 400°C, and / or at most 600°C, preferably at most 550°C, more preferably at most 530°C.
12. A calcined powder-coated article (e.g., a calcined powder-coated article formed by the method of claim 10 or claim 11), comprising: a) a coated monolithic article, and b) a calcined powder coating on the coated monolithic article, wherein the coated monolithic product is a monolithic product coated with a wall coating, And the calcined powder coating contains inorganic particles and silica in a ratio between 65:1 and 1:
7.
13. A calcined powder coated article according to claim 12, wherein the ratio of inorganic particles to silica is between 13:1 and 1:2, preferably between 6:1 and 1:1.5, more preferably between 5:1 and 1:0.8, such as about 2:
1.
14. The calcined powder coated article according to claim 12 or claim 13, wherein the pore size of the calcined powder coating is in the range of 1 μm to 100 μm, preferably 1 μm to 50 μm, more preferably 1 μm to 20 μm or 5 μm to 20 μm.
15. A powder coated product according to any one of claims 1 to 7 or a calcined powder coated product according to any one of claims 12 to 14 for use in treating exhaust gas.
16. A vehicle exhaust system comprising the powder coated article according to any one of claims 1 to 7 or the calcined powder coated article according to any one of claims 12 to 14.
Citation Information
Patent Citations
Method for coating a filter substrate
EP3122458A2
Treatment of particulate filters
EP4013954A1
Method
US11192793B2
Diesel particulate filter
WO2011151711A1
Treatment of particulate filters
WO2021028691A1